Cost-optimal levels and energy performance certificates: Filling the gaps. (December 2020) - dos Reis, Alexandre Soares; Dias, Marta Ferreira
Abstract: The energy performance of buildings directive establishes that Member States must introduce minimum energy performance requirements for buildings and building components. Studies must be done based on a cost-optimal level methodology, considering the investment and operational costs to reach nearly Zero Energy Buildings. However, there is a lack of information on the European Union guidelines concerning social and environmental issues. The existent framework requires Member States to make the calculations based on an economic perspective — a macroeconomic level and a financial level. Thus, the three-pillars (social, economic, and environmental) conception of sustainability is not fulfilled in the implementation of the present cost-optimal levels methodology. Neither indoor environmental quality is considered nor the environmental impact of the embodied CO2 in building components. Apart from this, current energy performance certificates are only energy-related. However, they have the potential to track also indoor environmental quality and the global environmental impact of building components. A new approach, both for cost-optimal levels and energy performance certificates, considering indoor environmental quality and the embodied CO2 in building components through a life cycle assessment, could fill the social and the environmental gaps.